Heart failure prevalence and predictors in Turkey: HAPPY study [Türkiye'deki kalp yetersizliǧi prevalansi ve öngördürücüleri: HAPPY çalişmasi] - (:unkn) unknown (My University, 2012)
Objectives: The aim of this study was to determine the prevalence of heart failure (HF) in adult residents of Turkey based on echocardiography and N-terminal B type natriuretic factor. Study design: 4650 randomly selected residents aged ≥35 years were enrolled. Height, weight, waist and hip circumference, and blood pressure measurements were taken, and a 12-lead ECG was performed. Advanced age, hypertension (HT), diabetes mellitus (DM), obesity, and chronic renal failure (CRF) were assessed. History of any heart disease, any abnormal ECG, or an NT-proBNP ≥120 pg/mL was accepted as echocardiography indication. Patients with systolic and/or diastolic dysfunction, or NT-proBNP ≥2000 pg/mL were classified as having HF if their functional capacity was NYHA ≥Class II, and were classified as having asymptomatic left ventricular dysfunction (ASVD) if their functional capacity was NYHA <Class I. Results: The absolute and estimated prevalences were 2.9% and 6.9% for HF, and 4.8% and 7.9% for ASVD, respectively. Advanced age, male gender, history of heart disease, HT and CRF were independent predictors of HF. In patients with ejection fraction (EF) <50%, HF prevalence was higher in men, while HF prevalences were higher in women when EF≥50%. In global sum, HF and ALVD prevalence were similar in male and females. Conclusion: The prevalences of HF and ASVD are higher in Turkey when compared with western countries, despite a younger Turkish population. The established predictors of HF are valid for Turkey as well. There is a significant ASVD population in Turkey with similar characteristics and risk factors to HF. Focusing on the early detection and treatment of ASVD may prevent the progression to HF, and therefore would decrease the prevalence of HF in Turkey.
Keywords: Biological markers; Echocardiography; Heart failure/epidemiology/etiology; Natriuretic peptide, brain/blood; Turkey/epidemiology